Contraceptive use and unmet need for family planning among HIV-positive women: A hospital-based study - Preeti Dugg; Pragti Chhabra; Arun Kumar Sharma (Wolters Kluwer Medknow Publications, 2020)
Background: For women living with HIV who do not want to become pregnant or who wish to delay pregnancy, contraception has the added public health benefit of reducing the number of infants who might acquire HIV. The unmet need for contraception must be addressed to prevent unintended pregnancies among HIV-positive women and consequently mother-to-child transmission of HIV. Objectives: The objectives of this study were to assess the contraceptive usage and its various determinants and to find out the unmet need for family planning among HIV-positive women. Methods: This was a cross-sectional descriptive hospital-based study conducted among 235 HIV-positive women attending the ART center of a medical college. Data were collected using a questionnaire-containing sociodemographic details, obstetric history, treatment information, contraceptive usage, and their fertility desires. Data analysis was performed using MS Excel and the SPSS version 20.0 using frequencies, Chi-squared test, and multiple logistic regression. Results: The mean (standard deviation) age of the study participants was 28.8 (5.5) years. Majority (96.6%) of them were married and were illiterate (34.4%). The prevalence of unmet need for family planning was found to be 17%, and the prevalence of consistent contraceptive use was 74.5%. The most common family planning method used by women was male condom. Not having HIV-positive children, HIV-negative partner, and discussing contraceptive with partner were observed to be significant predictor of consistent contraceptive use on multiple logistic regression. Conclusion: There is a need to boost family planning counseling and address the unmet need and contraceptive use among HIV-infected women.